Family Counseling on Parenting in The Prevention of Adolescent Bullying Behavior: A Literature Review - Saputra, Rizky Lukman; Susanto, Tantut; Rasni, Hanny; Kurdi, Fahruddin (Journal of Rural Community Nursing Practice, 2024)
Background: Bullying is aggressive behavior that often occurs among teenagers. Bullying has negative consequences such as threatened well-being and mental health that puts its victims at risk of committing suicide. A total of 37,381 child abuse cases occurred during 2011-2018 in Indonesia. Family dynamics and relationships reflected through parental parenting have not shown significant changes in the character building of the younger generation. Purpose: The purpose of this study is to describe family counseling about parenting in the prevention of adolescent bullying behavior. Methods: There are 11 articles sorted from 5 electronic journal databases: ScienceDirect, PubMed, Springerlink, ProQuest, and Google Scholar. The following combination of search terms is "Family Counseling", "Parenting", "Bullying behavior", and "Adolescent". The inclusion criteria of the article are the study population: adolescents aged 11-19 years; the article published from January 2017 to April 2022, discusses family involvement in settlement of traditional adolescent bullying through family counseling. Results: The results showed that the family is the primary source of support for every problem in the family. The family plays a crucial role in forming the child's behavior. Aggressive behavior arises from parenting that does not prioritize the child's rights. Family counseling on parenting in preventing adolescent bullying behavior is a process of active interaction between counselors, parents, and children with efforts to improve parent-child communication in achieving nonaggressive parenting that supports adolescent growth and development. Conclusions: This study can provide an overview of counseling interventions with families and adolescents regarding preventing bullying behavior using communication improvement strategies and parenting modifications.